Addition of high-intensity interval training to a moderate intensity continuous training cardiovascular rehabilitation program after ischemic cerebrovascular disease: A randomized controlled trial - Lapointe, Thalia; Houle, Julie; Sia, Ying-Tung; Payette, Marika; Trudeau, François (Frontiers in Neurology, 2023)
Moderate intensity continuous training (MICT) is usually recommended for stroke or transient ischemic attack (TIA) patients. High intensity interval training (HIIT) has emerged as a potentially effective method for increasing cardiorespiratory fitness (CRF) among clinical populations. Its effectiveness remains to be demonstrated after stroke. A combined program of HIIT and MICT was designed to create a realistic exercise program implemented for a clinical setting to help patients become more active. Purpose: This study aimed to compare the effects of a 6-month exercise program with either MICT only or a combination of HIIT and MICT and a control group in terms of CRF, cardiovascular risk factors, functionality, cognitive function (Montreal Cognitive Assessment) and depression markers (Hospital Anxiety and Depression Scale). Methods: This randomized controlled trial started with 52 participants (33 men and 19 women, mean age: 69.2 ± 10.7) divided into 3 groups: HIIT+MICT combined, MICT, and control. Both exercise groups consisted of 4 weekly sessions including supervised and at-home exercise. Outcomes were assessed at T0 (baseline measure), T6 (end of exercise protocols) and T12 (follow-up), 40 participants having completed the 12-month follow-up. Results: At T6, both HIIT+MICT and MICT programs provided a similar increase of CRF (3 ml·min-1·kg-1) from baseline (p<0.01), while the control group showed a global slight decrease. Despite some decrease of CRF at T12 compared to T6, improvement persisted 6 months post-intervention (HIIT+MICT: p<0.01 and MICT: p<0.05). The control group decreased compared with baseline (p<0.05). The two exercise programs induced a comparable increase in self-reported physical activity and a decrease in anxiety and depression markers. Participants in HIIT+MICT and MICT programs declared a good degree of acceptability assessed by the Acceptability and Preferences Questionnaire. Conclusion: A 6-month HIIT+ MICT combined program and a standard MICT program induced similar improvements in CRF, self-reported physical activity and anxiety and depression markers among patients with prior ischemic stroke or TIA compared with a control group. These effects appear to persist over time. Addition of HIIT was safe and considered acceptable by participants. Our results do not support any superiority of the combination HIIT+MICT nor disadvantage vs. MICT in this population.